Supervised attention for answer selection in community question answering - Thanh Thi Ha; Atsuhiro Takasu; Thanh Chinh Nguyen; Kiem Hieu Nguyen; Van Nha Nguyen; Kim Anh Nguyen; Son Giang Tran (IAES International Journal of Artificial Intelligence (IJ-AI), 2020)
Answer selection is an important task in Community Question Answering (CQA). In recent years, attention-based neural networks have been extensively studied in various natural language processing problems, including question answering. This paper explores matchLSTM for answer selection in CQA. A lexical gap in CQA is more challenging as questions and answers typical contain multiple sentences, irrelevant information, and noisy expressions. In our investigation, word-by-word attention in the original model does not work well on social question-answer pairs. We propose integrating supervised attention into matchLSTM. Specifically, we leverage lexical-semantic from external to guide the learning of attention weights for question-answer pairs. The proposed model learns more meaningful attention that allows performing better than the basic model. Our performance is among the top on SemEval datasets.